Cybersecurity Awareness among Women and Youth E-commerce Entrepreneurs in Bangladesh: An Exploratory Factor Analysis - Shabbir, Malik Shahzad; Karim, Fariha; Zayed, Nurul Mohammad; Monir, Md. Serajum; Bipasha, Munmun Shabnam; Edeh, Friday Ogbu; Alhebri, Adeeb; Jaradat, Mohammad; Bansal, Ajay; Said, Laila Refiana (International Review of Management and Marketing, 2026)
The issue of cybersecurity has taken the center stage among e-commerce business people especially in developing nations where the level of digital adoption is growing fast, with little awareness. This paper examines the hidden facets of cybersecurity awareness among the women and young e-commerce entrepreneurs in Bangladesh, which promotes gender equality in entrepreneurship. A quantitative method was employed to gather data on 244 respondents using a structured survey and an analysis of the data using Exploratory Factor Analysis (EFA) through SPSS. The findings indicate that cybersecurity awareness is a multidimensional concept that consists of three crucial variables, including cybersecurity awareness and risk perception, digital literacy and security practices, and cybersecurity knowledge with training and institutional support are needed for decent work and economic growth of SME entrepreneurs. Of these, the risk perception was found to be the strongest dimension, which means that the perception of the cyber threats by entrepreneurs is one of the most influential factors that determine their security behavior. The results also indicate the need to lay emphasis on digital literacy as a tool of facilitating safe online activity, as well as identify the gaps in formal education and institutional resources. The research will add value to the current body of literature, as it offers a unified model of cybersecurity awareness in the scenario of women and youth entrepreneurship in a developing economy, all these will reduce inequalities in SME sector.